SOSIALISASI DAN PEMETAAN KELAYAKAN USAHA MIKRO KECIL MENENGAH DI KABUPATEN SUBANG - Estu Widarwati; Devy Widya Apriandi; Nunik Nurmalasari; Bismantara Bismantara; Kuncorosidi Kuncorosidi; Mutqi Sopiawadi; Tigin Lugiani; Gugyh Susandy (Gapura (Garba Pembangunan Masyarakat), 2024)
The level of contribution to the performance of SMEs is needed by the Subang regional government as a booster of the Subang economy, but the fact is that the contribution of MSME performance in Subang Regency has not been evenly distributed which is possible due to differences in information, knowledge, and access to capital. The Covid-19 pandemic period triggered a decline in MSME performance and an increase in the risk of bankruptcy. Business feasibility is an important point for MSMEs to decide on the choice of strategy to survive in competition. Errors in analyzing business performance can cause MSMEs to fall due to decision errors such as segment determination errors, inability to compete, and losses due to poor financial management. The practice of socialization and mapping of the business feasibility of Subang MSMEs is needed by academics, practitioners, and local governments to information on the constraints and obstacles to the performance of Subang SMEs. The implementation of socialization practices and business feasibility mapping was carried out in August 2020 with 30 randomly selected respondents in Subang Regency whose businesses have been running for at least 2 (two) years. The stages of implementing activities are the delivery of material through workshops, structured questionnaires, and feedback evaluation with quantitative, descriptive, and exploratory approaches. The results of socialization and mapping practices show the main obstacles to MSME business in Subang Regency based on rankings, namely capital, product/service marketing, human resources, and fulfillment of formal licenses. Furthermore, MSMEs in Subang Regency need assistance in improving performance to be sustainable both financially and non-financially, including the fields of marketing products/services such as digital marketing, finance in the form of simple recording and accounting, HR management through increasing employee skills and competencies according to the business field, and assistance in the formal licensing application process.